2011
DOI: 10.2478/v10182-011-0024-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Paris quadrifolia Extract and Isolated Saponin Fractions Against Human Tumor Cell Lines

Abstract: Steroidal saponins isolated from many plant species belonging to Monocotyledones display potent cytotoxic activity towards many human tumor cells. We examined the cytotoxic effects of crude Paris quadrifolia extract for the first time, testing isolated saponin-rich fractions against four different human cell lines using the [(3-(4,5-dimethylthiazol-2-yl)]-2,5-diphenyltetrazolium bromide (MTT) assay. Cytotoxic activity was tested against human promyelocytic leukemia (HL-60) cells, human cervical adenocarcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It has been reported that saponins possess potent cytotoxic activity. [37] The general lack of cytotoxicity observed in this study is confirmed by literature. Apu et al [35] reported negligible in-vitro cytotoxicity of the n-hexane, ethyl acetate and methanol extracts of the aerial parts of the plant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been reported that saponins possess potent cytotoxic activity. [37] The general lack of cytotoxicity observed in this study is confirmed by literature. Apu et al [35] reported negligible in-vitro cytotoxicity of the n-hexane, ethyl acetate and methanol extracts of the aerial parts of the plant.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to treatment with extracts, treatment with saponin resulted in significant cellular damage and death. It has been reported that saponins possess potent cytotoxic activity . The general lack of cytotoxicity observed in this study is confirmed by literature.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] The plant occurs in deciduous forests in Poland and studies of this species are conducted at present. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%